Misalignment of the jet and the normal to the dusty torus in the broad absorption line QSO FIRST J155633.8+351758 - Reynolds, Cormac; Punsly, B.; O'Dea, C. (Institute of Physics Publishing Ltd., 2013)
We performed Very Long Baseline Array observations of the broad absorption line quasar FIRST J155633.8+351758, "the first radio loud BALQSO." Our observations at 15.3 GHz partially resolved a secondary component at position angle (P.A.) 35°. We combine this determination of the radio jet projection on the sky plane, with the constraint that the jet is viewed within 143 of the line of sight (as implied by the high variability brightness temperature) and with the P.A. of the optical/UV continuum polarization in order to study the quasar geometry. Within the context of the standard model, the data indicates a "dusty torus" (scattering surface) with a symmetry axis tilted relative to the accretion disk normal and a polar broad absorption line outflow aligned with the accretion disk normal. We compare this geometry to that indicated by the higher resolution radio data, brightness temperature, and optical/UV continuum polarization P.A. of a similar high optical polarization BALQSO, Mrk 231. A qualitatively similar geometry is found in these two polar BALQSOs; the continuum polarization is determined primarily by the tilt of the dusty torus.